2018
DOI: 10.1007/s11916-018-0710-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Management of Headache in Pituitary Tumors

Abstract: Recent prospective evaluations indicate that risk factors for development of headache in the setting of pituitary adenoma include highly proliferative tumors, cavernous sinus invasion, and personal or family history of headache. Migraine-like headaches are the predominant presentation. Unilateral headaches are often ipsilateral to the side of cavernous sinus invasion. In summary, this paper describes how the size and type of pituitary tumors play an important role in causation of headaches. Pituitary adenoma-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Other interesting findings of the study by Lima Carvalho et al are that it is not as yet possible to identify hypothyroid patients who are susceptible to developing HAH and that the clinical characteristics of HAH did not differ between patients with subclinical and overt hypothyroidism. Additionally, in the case of non‐responders after 3 months of hormone replacement, Lima Carvalho et al suggested neuroimaging investigation, to differentiate from other conditions related to low levels of thyroid hormones, and a combination of preventive drugs with levothyroxine when no secondary cause is identified.…”
Section: Discussionmentioning
confidence: 99%
“…Other interesting findings of the study by Lima Carvalho et al are that it is not as yet possible to identify hypothyroid patients who are susceptible to developing HAH and that the clinical characteristics of HAH did not differ between patients with subclinical and overt hypothyroidism. Additionally, in the case of non‐responders after 3 months of hormone replacement, Lima Carvalho et al suggested neuroimaging investigation, to differentiate from other conditions related to low levels of thyroid hormones, and a combination of preventive drugs with levothyroxine when no secondary cause is identified.…”
Section: Discussionmentioning
confidence: 99%
“…17 Since headaches linked to pituitary adenomas can mimic primary headache disorders, particularly the trigeminal autonomic cephalalgias, it is important to maintain a high index of clinical suspicion for a secondary process in a patient with refractory headaches. 3,15 If imaging fails to reveal an abnormality, there is benefit in a hormone panel and medical management with alternative pharmacotherapy than usually prescribed for headache.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms have been proposed for pituitary adenomas causing CH-like attacks, including tumor invasion into adjacent areas, 3, 7 9,1517 mass effect/tumor size, 3,7,10,11,15,16 hormonal secretion, 3,15 17 and inflammation or irritation of pain-sensitive structures, such as the meninges. 3,16,17 In our case and one other, 12 CH-like attacks were initially associated with normal imaging that later revealed a macroadenoma. Unlike our case, the other report was of a single type of headache with typical features of CH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations